Assessment of the effect of inversion ankle sprain on the velocity capabilities of the dorsal and plantar flexors of the foot in a group of women - Kopytko, Agnieszka; Chwała, Wiesław (Physiotherapy Review, 2023)
The ankle joint, also known as the talocrural joint, classified as a hinge synovial joint, is formed by the complex articulation of the ankle, tibia, and fibula. The tripartite junction of the ankle, tibia, and fibula combine to form the ankle joint, which demonstrates the complexity of the human skeletal system. Up to 30% of all sports injuries are injuries to the ankle joint, and ankle sprains account for up to 70% of all injuries. Aims: This study aimed to assess the effect of inversion talocrural joint (ankle joint) sprain on the velocity capabilities of the soleus and dorsiflexor muscles of the feet in a group of women. Material and methods: The study group consisted of 33 young women. The experimental group consisted of 16 women with a history of inversion ankle sprain injury, while the control group consisted of 17 women without ankle sprain injury. All participants were tested using the ZPS4-U "JBA STANIAK" force measurement set. Results: In our study, the mean values of the maximum force gradient increase (MFGI) in the control group were higher for the dorsal flexors by approximately 13% compared to the plantar flexors. Variables characterizing the MFGI within the control and experimental groups and in intergroup analyses showed no significant statistical differences (p>0.05). Conclusions: Inversion sprain of the ankle joint does not affect the achieved velocity capabilities of the dorsal and plantar flexors of the foot in the study group of women. Taking into account the parameters analyzed, no statistically significant differences were found.